Skeletal-Related Events (SRE) in Prostate Cancer: A Report of Two Cases - Diatmika, Anak Agung Ngurah Oka; Hardjowijoto, Sunaryo (Folia Medica Indonesiana, 2021)
A skeletal-related event (SRE) is an event occurring due to bone metastasis in prostate cancer. SREs are usually marked by pain, pathological fractures, spinal cord compression, hypercalcemia, or bone metastasis requiring radiotherapy or operation. Case I: A 64-year-old male was diagnosed with a pathological fracture of the left femur. Thoracal CT scan showed osteoblastic lesions in the thoracal vertebrae, sternum, clavicle, and humeral head. Spinal MRI showed destruction of the cervical to sacral vertebral bodies. The histopathological result with Adenocarcinoma Gleason scores 8 (4+4) and an initial prostate-specific antigen (PSA) level of 689,7 ng/dL. Afterward, subcapsular orchiectomy was performed. However, his PSA level was still high (>100 ng/dL) even after serum testosterone had reached a castration level. The patient died during the first chemotherapy using docetaxel. Case II: A 61-year-old male was diagnosed with inferior paraplegia and neurogenic bladder, paraparesis, urinary retention, and pain in the flank area. Spinal MRI showed a pathological compression fracture of the 8th thoracic vertebrae. Thoracal CT scan showed costal and 8th thoracal vertebrae destruction as well as multiple nodules in the lungs. Histological results with Adenocarcinoma Gleason score 9 (4+5) and an initial PSA level of 750 ng/dL. Afterward, subcapsular orchiectomy was performed. Serum testosterone reached castration level with the lowest PSA concentration of 21.6 g/dL. The patient declined chemotherapy and agreed to palliative treatment. He died one year after diagnosis. A high PSA level (>500 ng/dL) could potentially be used as a predictor for severe SRE.